Client's perceptions of the oncology social work service at cancer care - Variawa, Tasneem (Department of Social Development, 2020)
This study explored clients’ perceptions of the oncology social work services offered at three Cancercare practices in Cape Town. It considered their motivation for using the service as well as their overall experience of the service. Positive aspects as well as the challenges encountered with the service were examined concerning the frequency and nature of intervention, and their professional relationship with the social workers. The research was conducted using a qualitative research design, more specifically phenomenology. Sixteen participants were selected using purposive sampling by the researcher. They were interviewed face-to-face using a semi-structured interview schedule. The data obtained were analysed using qualitative methods. The findings of this study highlighted the value of a psychosocial service accessible to cancer patients. Psychosocial responses to diagnosis and treatment included the need for information, psychological support for the patient and family, and an assorted range of practical needs. Findings also highlighted the complexities surrounding public perceptions of social workers and psychologists, and the blurred boundaries between the professions in terms of services offered. Participants identified six aspects of the service that were helpful. The challenges encountered with the service were presented in terms of the lack of clarity on the role of the social worker and the need for specific information about the service and external resources. Recommendations were made around the distribution of information within the practice and participants requested regular post-treatment support. Further recommendations were made in terms of professional contact within a public setting, early intervention and future research.